Answer:
64
Step-by-step explanation:
;)
Answer:1. GCF of the group ( 6 x - 3 ) is 3.
2. The common binomial factor is 2 x - 1.
3. The factored expression is: ( 2 x - 1 ) ( 7 x + 3 ).
Step-by-step explanation:
14 x² + 6 x - 7 x - 3 =
= ( 14 x² - 7 x ) + ( 6 x - 3 ) =
= 7 x ( 2 x - 1 ) + 3 ( 2 x - 1 ) =
= ( 2 x - 1 ) ( 7 x + 3 )
If u take you answer as x and do the problem u will see that they are equal so u would have to have a different answers for x or say -6.1 is greater than or equal to -17.4 + 11.3